Religious Sounds Beyond the Global North: Senses, Media and Power - Ahmed, Bayes; Aryandari, Citra; Coppola, Marco Romano; Dean, Kenneth; Eisenlohr, Patrick; Farzana, Kazi Fahmida; Graves, Eben; Hackett, Rosalind I. J.; Hackett, Rosalind I. J.; Halder, Epsita; Henley, David; Hsin-chun Lu, Tasaw; et al. (Global Asia, 2024)
What makes sounds “religious”? How are communities shaped by the things they hear, play, or listen to? This book foregrounds connections between sounds, bodies, and media in the private and public life of communities beyond the Global North, analyzing diverse configurations of the category of sound and various sonic ontologies to usher in a more inclusive global anthro-history of religious sounds. This edited volume implements a “sonic turn” in the study of religion by engaging with a diversity of auditory, musical, and embodied practices. Dislodging the Global North as the main point of reference for studies on religious sound, this volume proposes an acoustemology of the post-secular with an emphasis on Asia as method. Unsettling and expanding existing discussions on senses, media, and power, editors Carola E. Lorea and Rosalind I. J. Hackett present religious sounds as co-creating subjectivities and collectivities that coalesce around audible aesthetic formations. This volume demonstrates that religious sounds are not only produced by certain religious traditions but also produce communities, shaping the self and sensitivity of those who participate.